Spectrometric imaging of sub-hourly methane emission dynamics from coal mine ventilation. (1st April 2023) - Knapp, M; Scheidweiler, L; Külheim, F; Kleinschek, R; Necki, J; Jagoda, P; Butz, A
Abstract: Anthropogenic methane (CH4 ) emissions contribute significantly to the current radiative forcing driving climate change. Localized CH4 sources such as occurring in the fossil fuel industry contribute a substantial share to the anthropogenic emission total. The temporal dynamics of such emissions is largely unresolved and unaccounted for when using atmospheric measurements by satellites, aircraft, and ground-based instruments to monitor emission rates and verify reported numbers. Here, we demonstrate the usage of a ground-based imaging spectrometer for quantifying the CH4 emission dynamics of a ventilation facility of a coal mine in the Upper Silesian Coal Basin, Poland. To this end, we deployed the imaging spectrometer at roughly 1 km distance from the facility and collected plume images of CH4 column enhancements during the sunlit hours of four consecutive days in June 2022. Together with wind information from a co-deployed wind-lidar, we inferred CH4 emission rates with roughly 1 min resolution. Daily average emission rates ranged between 1.39 ± 0.19 and 4.44 ± 0.76 tCH4 h −1, 10 min averages ranged between (min) 0.82 and (max) 5.83 tCH4 h −1, and puff-like events caused large variability on time scales below 15 min. Thus, to monitor CH4 emissions from such sources, it requires measurement techniques such as the imaging spectrometer evaluated here that can capture emission dynamics on short time scales.